Colonization Ability of Biological Control Agent Tricoderma spp on Cocoa Pod and Seedling - Rina Sriwati; Tjut Khamzurni; Elvira Iskandar; Mitra T. A. Lestari (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Some  of Trichoderma species  as  antagonistic  fungi  are  usually  considered  soil  microorganism, They  colonize  plant  roots,  some- times  forming  a  symbiotic  relationship.  Three  species  of Trichoderma (T. virens, T. harzianum and T. asperellum) have been inoculated on cacao seedling and  cocoa  pod. Trichoderma species  can  be  re-isolated  from  surface  sterilized  cacao  seedling, including the stem and leaf, root, and pod then observed their colonization ability. Fungal hyphae were observed under the microscope emerging from the leaf, steam, root of seedling and pod as soon as 1 day after their isolation from surface sterilized cacao seedling and pod. All Trichoderma species  were  able  to  enter  and  make  colonization.    The  highest  percentage  of  colonization occurred  in  the T.  harzianum by  73.3%  (leaves),  46.7%  (trunk)  and  86.7%  (roots).  While colonization  on the  skin  cocoa  pod  (epidermis)  also  has  a  different  percentage,  the  highest percentage indicated in the treatment of T. harzianum by 63.3%. We conclude that T. harzianum better  biological  control  agent  base  on  their  ability  to  colonize  all  part  of  seedling and  pod. Trichoderma species into the cacao stem, leaf, root and pod allowing systemic colonization of this tissue.